The roles of river discharge and sea ice melting in formation of freshened surface layers in the Kara, Laptev, and East Siberian seas - Osadchiev, Alexander; Kuskova, Ekaterina; Ivanov, Vladimir (Frontiers in Marine Science, 2024)
Wide areas of the Siberian Arctic shelf are covered by freshened surface water layers, which are among the largest in the World Ocean. River discharge is the main freshwater source for formation of these layers, therefore, they are commonly referred to as river plumes (the Ob-Yenisei plume in the Kara Sea and the Lena plume in the Laptev and East Siberian seas). The contribution of sea ice meltwater (SIM) to the Ob-Yenisei and Lena plumes is believed to be small, albeit, its actual volume remains unknown. In this study, we use a novel dataset of satellite-derived sea ice thickness in the Arctic Ocean during the melt period to quantify the annual volume of SIM, which was received by the Ob-Yenisei and Lena plumes during 2012-2020. We reveal that SIM is a significant source for the Lena plume providing on average 20% of total annual freshwater content. Moreover, the share of SIM in the Lena plume shows large inter-annual (14-29%) variability, i.e., during certain years SIM provides almost one third of freshwater volume of the Lena plume. This variability is governed by inter-annual variability of ice thickness, as well as seasonal variability of sea ice melting conditions. Conversely, the contribution of SIM to the Ob-Yenisei plume is relatively low (8% on average) and its total annual share varies from 6 to 11% during the study period. This difference is mainly caused by significantly smaller area of the Ob-Yenisei plume as compared with the Lena plume. The forecasted earlier onset of ice melting in the Arctic Ocean in future decades due to climate change could decrease the contribution of SIM to the Ob-Yenisei plume, while its influence on the Lena plume remains unclear.